Hubungan Dukungan Suami Dengan Kejadian Baby Blues Syndrome Pada Ibu Nifas Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2026 - Hikmah Kasih; Liya Lugita Sari; Tita Septi Handayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Baby blues syndrome is rarely addressed in Indonesia because it is considered unimportant and merely a side effect of postpartum fatigue. The Indonesian Health Survey (2023) found that 15.5 million postpartum mothers exhibited signs of sadness and gloom, with 1.1 million cases of baby blues. In Bengkulu Province, there were 479 cases of baby blues. The purpose of this study was to determine the relationship between husband's support and the incidence of baby blues syndrome in postpartum mothers in the Telaga Dewa Community Health Center (Puskesmas) area, Bengkulu City, in 2026. The research method used was descriptive research with a cross-sectional approach. The sampling technique used purposive sampling, with a sample size of 86 postpartum mothers in the Telaga Dewa Community Health Center (Puskesmas) area, Bengkulu City, in 2026. Data analysis used the Chi-Square test with a significance value of p < 0.05. The results of the univariate analysis showed that the majority of respondents (64%) did not experience baby blues syndrome, and the majority (75.6%) had supportive husbands. The bivariate analysis revealed a relationship between husband support and the incidence of baby blues syndrome in postpartum mothers in the Telaga Dewa Community Health Center (Puskesmas) work area in Bengkulu City in 2026 (p-value 0.000). There was a relationship between husband support and the incidence of baby blues syndrome in postpartum mothers in the Telaga Dewa Community Health Center (Puskesmas) work area in Bengkulu City in 2026. The researchers recommend that Puskesmas develop postpartum maternal mental health counseling and education programs to ensure optimal support for postpartum mothers, thus preventing the incidence of baby blues syndrome.